2015
DOI: 10.1038/srep10990
|View full text |Cite
|
Sign up to set email alerts
|

MoS2 Heterojunctions by Thickness Modulation

Abstract: In this work, we report lateral heterojunction formation in as-exfoliated MoS2 flakes by thickness modulation. Kelvin probe force microscopy is used to map the surface potential at the monolayer-multilayer heterojunction, and consequently the conduction band offset is extracted. Scanning photocurrent microscopy is performed to investigate the spatial photocurrent response along the length of the device including the source and the drain contacts as well as the monolayer-multilayer junction. The peak photocurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
95
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 40 publications
10
95
0
Order By: Relevance
“…The change of I–V curves on vertical of MoS 2 /Pt junction is attributed to the increase of SBH, which is consistent with the change of surface potential difference between MoS 2 and Pt substrate. The variation of SBH at MoS 2 /Pt junctions is 0.04 eV (Figure b) with the increase of light intensity, which is consistent with the variation of ΔCPD (0.049 eV, Figure ) between MoS 2 and Pt substrate.…”
Section: Discussionsupporting
confidence: 79%
“…The change of I–V curves on vertical of MoS 2 /Pt junction is attributed to the increase of SBH, which is consistent with the change of surface potential difference between MoS 2 and Pt substrate. The variation of SBH at MoS 2 /Pt junctions is 0.04 eV (Figure b) with the increase of light intensity, which is consistent with the variation of ΔCPD (0.049 eV, Figure ) between MoS 2 and Pt substrate.…”
Section: Discussionsupporting
confidence: 79%
“…[22][23][24] This layer-dependent electronic structure therefore offers a distinct approach for designing the MoS2 junction based on homogeneous material of the TMDCs. [25][26][27][28] In this work, we fabricated atomic thin MoS2 junction phototransistors with different MoS2 layers and studied their photoresponse behavior at different source-drain bias and gaseous environment. The difference of band gap in different thickness of few layer MoS2 was utilized to create a built-in electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the comparison of experimental results with finite‐element device simulations, a type‐II band alignment between monolayer and multilayer MoS 2 was suggested, and the junction‐induced current at zero bias was ascribed to the hot‐electron contribution. However, in another study on MoS 2 lateral‐thickness heterojunctions, Tosun et al observed a photocurrent dominated by the MoS 2 monolayer–multilayer interface rather than the MoS 2 –metal Schottky contacts . Furthermore, they attributed this photocurrent to the formation of a type‐I band alignment at the MoS 2 heterointerface.…”
Section: Photovoltaics In the Lateral Configuration Of 2d Materialsmentioning
confidence: 99%
“…A well‐known nature of 2D layered materials is their thickness‐dependent (or layer‐number‐dependent) bandgaps . Such dependence implies energy‐band discontinuities at the interface of different‐layer‐number films, forming spontaneously a lateral heterojunction distinct from the conventional ones . Study of this kind of structure is likely to expand the realms of the diverse applications of 2D materials, including photovoltaics.…”
Section: Photovoltaics In the Lateral Configuration Of 2d Materialsmentioning
confidence: 99%